Retraction Note: The lincRNA-ROR/miR-145 axis promotes invasion and metastasis in hepatocellular carcinoma via induction of epithelial-mesenchymal transition by targeting ZEB2 - Chen Li; Lu Lu; Bing Feng; Kai Zhang; Siqi Han; Daorong Hou; Longbang Chen; Xiaoyuan Chu; Rui Wang (Scientific Reports, 2023)
Editor's Note: this Article has been retracted; the Retraction Note is available at https://doi.org/10.1038/s41598-023-32251-x